KERUSAKAN BLEEDING PADA LAPISAN BERASPAL AKIBAT PENGARUH TEMPERATUR ASPAL SAAT PENCAMPURAN - Kurniadjie Kurniadjie (Jurnal Jalan-Jembatan, 2007)
Bleeding/flushing is a defect which is predicted caused by part or all aggregate in mixture covered by over thickness film, this defect might be caused by higher percentage of asphalt in mixture or other reasons. To evaluate bleeding defect, asphalt content from bleeding pavement is extracted, laboratory experiment also conducted to find other possible causes such as too thick of asphalt film in aggregate. This can be evaluated in laboratory by varying asphalt temperature so that its effect on characteristic of mixture can be obtained. Base on asphalt extraction test of bleeding pavement sample, percentage of asphalt content is 5.93% which still conform with the tolerance of optimum asphalt content Job Mix Formula (JMF) 5.7% - 6.3%. Beside, gradation of aggregate is also still within tolerance. Laboratory study of varying asphalt temperature shows that low asphalt temperature will produce low density, Voids Filled Bitumen (VFB), Stability and Marshall Quotient. On the other hand, Voids in Mineral Aggregate (VMA) and Void in Mix (VIM) are both high. Based on the above parameter trend and asphalt film thickness in 10.4 micron of aggregate for asphalt temperature which does not conform with specification. It can be indicated that asphalt acts as lubricati on instead of binder and filler of void in asphalt mixture. That could be accured, if quality control was not properly conducted so that asphalt temperature become uncontrolled. Keywords : Bleeding, Asphalt Content, Temperature.